Hilgardite polytype distribution in Sussex, New Brunswick evaporite deposits. (April 2014) - Grice, J. D.; Rowe, R.
Abstract: Hilgardite, Ca2 B5 O9 Cl·H2 O, has a zeolite-type framework structure consisting of cross-linked (010) layers of borate sheets having the fundamental building block (FBB) = 2Δ3☐:<Δ2☐>-<Δ2☐>. These layers are polar and the orientation, plus the number of layers in a sequence, determine the polytype. To date three hilgardite polytypes have been described: hilgardite-1 A, -3 A and -4 M . A reliable means of polytype identification by micro X-ray powder diffraction (mXRPD) is outlined. Two polytypes are identified in the Sussex New Brunswick potash deposits: hilgardite-1 A and -3 A . Both cells are refined with XRPD data: hilgardite-1 A, a 6.456(1), b 6.558(1), c 6.295(1) Å, α 61.62(1), β 118.76(1), γ 108.82(2)°, V 205.23(4) Å 3 and hilgardite-3 A, a 17.484(6), b 6.487(3), c 6.321(3) Å, α 60.78(3), β 79.58(3), γ 84.16(3)°, V 615.3(3) Å 3 . Hilgardite polytype assemblages are determined for 24 Millstream deposit core samples and 43 Penobsquis deposit core samples. The Millstream deposit occurs as an isolated, inner basin during evaporite formation. Borate formation from this marine environment was during the last stages of evaporation. Simple Mg-Ca borates precipitated from this highly saline brine. It underwent subsequent minor folding and all hilgardite samples are the hilgardite-1 A polytype. The Penobsquis deposit occurs as an open fore-basin. This larger, less saline basin also precipitated borate minerals during the final stages of evaporation. The borate assemblage here is much more complex with borate minerals that have essential Ca, K, Fe, Mg and Sr. This deposit was subjected to major folding and recrystallization. Both hilgardite-1 A and -3 A occur here. Polytype-3 A is concentrated in areas of maximum folding and it is proposed that pressure is the main control of hilgardite polytypes. Strontium substitution has no effect on polytype formation.